Tele-orthodontic as a recent solution in malocclusion treatment - Mansjur Nasir; Yunita Feby Ramadhany (Makassar Dental Journal, 2020)
Introduction: Malocclusion is a dental health problem that has a high prevalence rate. According to WHO, the periodic ranking is below dental caries and periodontal disease. The prevalence in Indonesia reaches 80%. Orthodontic treatment requires intensive time to control every month. This is an obstacle forcertain patients who have busy schedules and great distances from the clinic to the dentist clinic. In this context, orthodontics was invited to go forward using tele-orthodontic devices which is a term used for long-distance orthodontic treatment through information technology media, not through direct contact with individual contacts. Objective: To examine more deeply about tele-orthodontics as a solution in the treatment of malocclusion. Discussion: Dental MonitoringTM is a software-based program that enables practitioners to monitor the development of patient care remotely. Another advantage is closer management through remote monitoring, saving time, transportation costs, and increasing patient comfort. Conclusion: Tele-orthodontics can be used as a current solution to treatment for malocclusion.